2022
DOI: 10.3390/en15062050
|View full text |Cite
|
Sign up to set email alerts
|

Does Chinese Foreign Direct Investment (FDI) Stimulate Economic Growth in Pakistan? An Application of the Autoregressive Distributed Lag (ARDL Bounds) Testing Approach

Abstract: The objective of this paper is to ascertain the impact of Chinese FDI on economic growth in Pakistan. This study documents the exploration of the determinants of economic growth in Pakistan by emphasizing the significant role played by Chinese FDI and investments in renewable energy in particular. This paper employs time series data analysis to examine the relationship between GDP and Chinese FDI, inflation, trade openness, exchange rates, interest rates, remittances, and renewable energy consumption from 1990… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 44 publications
5
24
1
Order By: Relevance
“…In addition, FDI can help boost exports by expanding the capacity and competitiveness of domestic production. This result is consistent with the findings of multiple studies (Mehic et al, 2013;Alvarado et al, 2017;Hayat, 2017;Sultanuzzaman et al, 2018;Dinh et al, 2019; http://journal.uinjkt.ac.id/index.php/signifikan https://doi.org/10.15408/sjie.v12i1.29975 Shittu et al, 2020;Zeeshan et al, 2020;Mohamed et al, 2021;Nasir et al, 2021;Orji et al, 2021;Ahmad et al, 2022), which have found that an increase in FDI inflows can stimulate economic growth. In addition, Raza et al (2021) discovered that countries with high institutional quality tend to have stronger economic growth and more foreign direct investment (FDI) inflows.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, FDI can help boost exports by expanding the capacity and competitiveness of domestic production. This result is consistent with the findings of multiple studies (Mehic et al, 2013;Alvarado et al, 2017;Hayat, 2017;Sultanuzzaman et al, 2018;Dinh et al, 2019; http://journal.uinjkt.ac.id/index.php/signifikan https://doi.org/10.15408/sjie.v12i1.29975 Shittu et al, 2020;Zeeshan et al, 2020;Mohamed et al, 2021;Nasir et al, 2021;Orji et al, 2021;Ahmad et al, 2022), which have found that an increase in FDI inflows can stimulate economic growth. In addition, Raza et al (2021) discovered that countries with high institutional quality tend to have stronger economic growth and more foreign direct investment (FDI) inflows.…”
Section: Resultssupporting
confidence: 91%
“…Orji et al (2021) found that FDI can increase economic growth, and therefore governments should aim at attracting FDI in all sectors, particularly the industrial and service sectors. This result is supported by the findings of Ahmad et al (2022), who observed that FDI could drive economic growth. Gochero & Boopen (2020) found that FDI in the mining sector can increase economic growth in both the short and long terms.…”
Section: Introductionsupporting
confidence: 81%
“…To proceed, a VECM(2) is performed, which according to the inverse root of AR characteristic polynomial indicates satisfies the stability condition. 7 The Akaike Information Criterion (AIC) and the Final Prediction Error (FPE) also suggest a length of 2, and this is important for the lag specification, since the AIC and the FPE have been proven to be superior to any other criteria in case of small samples -60 observations and below-(Liew, 2004), such as in our case. This is because they minimize the possibility of the underestimation, while they maximize the chance of obtaining the true lag length (Liew, 2004).…”
Section: Vec Modelmentioning
confidence: 70%
“…A lag length of 2 is selected, as supported by the majority of the criteria. 7 For the sample period 1980-2018, the Johansen cointegration test supports three cointegrating equations between the variables at 5% level of significance using the Trace test, and two cointegrating equations at 5% level of significance using the max-Eigenvalue test. 8…”
Section: The Johansen Cointegration Testmentioning
confidence: 97%
See 1 more Smart Citation